Copper-catalyzed oxidative coupling of acids with alkanes involving dehydrogenation: facile access to allylic esters and alkylalkenes1. Issue 12 (11th February 2015) - Wang, Cheng-Yong; Song, Ren-Jie; Wei, Wen-Ting; Fan, Jian-Hong; Li, Jin-Heng
<x xml:space="preserve">Abstract</x> A new copper-catalyzed oxidative coupling of acids with alkanes for selective synthesis of allylic esters and alkylalkenes is described.